Effect of neurotensin on cultured mouse preimplantation embryos - HIRADATE, Yuki (J Reprod Dev, 2020)
Previously, we revealed that neurotensin (NTS) derived from the oviduct and uterus can function during fertilization. However, little is known about NTS actions on the pre-implantation embryo after fertilization. Here, we found that pro-Nts mRNA is expressed in the oviduct and uterus during when preimplantation embryos develop and an increase in mRNA level in the uterus is induced by human chorionic gonadotropin (hCG) treatment. Expression of mRNA for two NTS receptors, Ntr1 and Ntr3, was found throughout these stages, whereas Ntr2 mRNA was not detected, suggesting that NTS signaling occurred through NTR1 and NTR3. Supplementation of 1, 10, 100 or 1000 nM NTS to embryo culture medium after fertilization showed that 100 nM NTS significantly improved the blastocyst formation. In comparison, the total number of cells and inner cell mass ratio of blastocysts was not significant different between the 0 nM and 100 nM NTS treatment groups. These results indicate that NTS has a positive effect upon preimplantation embryo development in vitro.